2017
DOI: 10.1093/ckj/sfx111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of non-diabetic renal disease in type 2 diabetes patients

Abstract: BackgroundRenal involvement in type 2 diabetes is mainly due to diabetic nephropathy (DN). Nevertheless, a sizable proportion of diabetic patients could actually have nondiabetic renal diseases (NDRDs) or DN plus NDRDs. This study aimed to explore the pathological features of NDRD in diabetic patients and to assess the predictability of diagnosing NDRD (±DN) versus isolated DN on the basis of clinical parameters.MethodsMedical records of type 2 diabetes patients who underwent renal biopsy under suspicion of ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 35 publications
9
35
2
1
Order By: Relevance
“…Higher renal function was found to be a signi cant predictor in a recent study [9], showing eGFR ≥90 ml/min/1.73m 2 had OR of 6.38 (95% CI, 1.58-25.7). High HbA1c or fasting blood sugar were reported in a few studies [5,7]. Unlike previous reports [6, 9, 15], we could not nd any association of proteinuria levels with NDRD as the majority of our population already had macroalbuminuria.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Higher renal function was found to be a signi cant predictor in a recent study [9], showing eGFR ≥90 ml/min/1.73m 2 had OR of 6.38 (95% CI, 1.58-25.7). High HbA1c or fasting blood sugar were reported in a few studies [5,7]. Unlike previous reports [6, 9, 15], we could not nd any association of proteinuria levels with NDRD as the majority of our population already had macroalbuminuria.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies have only reported predictors, such as absence of DR, duration of diabetic mellitus (DM), degrees of proteinuria, Hemoglobin A1c (HbA1c), or levels of creatinine or GFR associated with NDRD, but none have mentioned the utility of a combined predictive probability [3,[7][8][9]. A clinical prediction score combines predictors in the model, informs clinicians and patients about disease probability, and can aid in decision-making [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it's difficult to define the onset of type 2 DM accurately; therefore, the known duration is less strongly related to DN [17,25]. Several studies still showed that DM duration was shorter in type 2 DM patients with NDRD than patients with DN [19,20,[28][29][30][31][32]. In our study, patients with NDRD ± DN had a shorter duration of DM than patients with isolated DN (Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…The difference in DM duration might come from patients without diabetic retinopathy, and the duration of DM is also a factor predicting the presence of NDRD within this subgroup. The presence of hematuria has been considered as one of the atypical features suggesting the presence of NDRD in the previous guidelines [25] and reports [16,28,30,[32][33][34][35][36][37]. However, there are also some studies suggesting that hematuria is not an uncommon finding in patients with typical DN (between 35 and 78%) and thus is not useful in predicting NDRD [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…(14) The tubulointerstitial changes in diabetic nephropathy are thought to be related to the renal microvasculature alterations, and it is generally held that they are attributed to chronic ischemia or hypoxia. (14) IHC studies of the kidney biopsies showed apoptotic pathology in the renal tubules. The outcome of renal tubular injury could be apoptosis of epithelial cells with mild injury and necrosis if the insult is severe.…”
Section: Discussionmentioning
confidence: 99%